Financial Determinants of Stock Prices in the Jakarta Islamic Index: Evidence from DER, PER, and DPS - Rohmah, Latifur; Ikram, Muhammad Fadhli Dzil; Hasanah, Nuryana Nurul (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction: Understanding how financial indicators drive stock prices in Sharia-compliant markets is essential for guiding informed and ethical investment decisions. This study examines the influence of three key financial performance measures—Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Dividend per Share (DPS)—on the stock prices of companies listed in the Jakarta Islamic Index (JII). As one of Indonesia’s premier Islamic indices, JII offers a distinctive setting where conventional financial metrics interact with the principles of Islamic finance. Methodology: A quantitative explanatory approach was employed using panel data from 20 companies consistently listed in JII between 2019 and 2023. Firms were selected based on consistent dividend distribution, complete financial reporting, and compliance with Sharia screening criteria. The Fixed Effect Model was chosen following Chow and Hausman tests. Model validity was confirmed through classical assumption tests, showing normality, no multicollinearity, no heteroskedasticity, and no autocorrelation. Results: The analysis reveals that PER (β = 62.43, p = 0.002) and DPS (β = 4.15, p < 0.001) exert a significant positive influence on stock prices, indicating that profitability expectations and dividend policies are decisive factors for investors. Conversely, DER (β = –305.78, p = 0.039) has a significant negative effect, suggesting that higher leverage is viewed unfavorably in Sharia markets due to restrictions on interest-based financing. The adjusted R² of 0.709 reflects strong explanatory power. Conclusion: Dividend policy and profitability expectations emerge as primary drivers of stock prices in JII-listed firms, while excessive leverage undermines market valuation. These findings offer practical guidance for corporate managers, policymakers, and investors aiming to strengthen Sharia-compliant investment strategies. Future studies may integrate macroeconomic variables or compare across global Islamic indices to broaden the insights.